State Finance Management With The Use Of Financial Accounting System Applications At The Agency Level In The Tni Au Environment In Order To Realize Transparency And Accountability - Sutanto, Adi; Hadi, Yulianto; Suwito, Suwito (CV RIFAINSTITUT, 2025)
State financial management in the Indonesian Air Force environment faces challenges in realizing transparency and accountability. This study aims to evaluate the use of the Agency Level Financial Accounting System Application in improving transparency and accountability of financial management in the Indonesian Air Force. This research method is descriptive qualitative with data collection techniques through in-depth interviews, observations, and documentation studies in various Indonesian Air Force work units that have implemented the Agency Level Financial Accounting System Application. The results of this study are that the implementation of the Agency Level Financial Accounting System Application in the Indonesian Air Force has increased transparency through more systematic recording of financial transactions that are easily accessible to related parties. Accountability has also been increased with the audit trail feature that allows detailed tracking of each financial transaction. The conclusion of this study is that the use of the Agency Level Financial Accounting System Application is effective in realizing transparency and accountability of financial management in the Indonesian Air Force environment, although there are still challenges that need to be overcome.